Influence of suction pressure of clay unsaturated soils on slope stability - M. A. Novgorodova; D. N. Gorobtsov; A. S. Ushakov (Известия высших учебных заведений: Геология и разведка, 2024)
Background. The main aspects of the influence of suction pressure on slope stability are considered; an example of calculations in the Plaxis software is presented. Specific features in the behavior of unsaturated and saturated soils are described. A model for describing the behavior of saturated soil under the influence of suction pressure is proposed.Aim. Soviet hydrophysic and soil scientists actively explored the relationship between capillary-sorption (structural or matrix) water pressure in the soil and humidity. However, the introduction of foreign methods and software based thereon into the engineering and geological practice of calculating the stability of slopes has raised the question about the influence of suction pressure of clay soils on the stability of slopes. Materials and methods. The main research material was loams of the Moscow glaciation. Simulation was carried out based on the Muallem — van Genuchten model.Results. The simulation results showed that suction pressure and capillarity directly affect the slope stability coefficient, provided that the similarity of other model parameters.